(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Purpose: This study conducts a comparative analysis of India’s Ram Van Gaman Path (RVGP) and Jyotirlinga Pilgrimage (JYTP) to evaluate their roles in shaping religious tourism, focusing on infrastructure, visitor satisfaction, and cultural relevance. Design/Methodology/Approach: A mixed-methods approach was employed, integrating literature review with empirical data from 105 pilgrims (50 RVGP visitors, 55 JYTP visitors). Statistical analysis, including independent samples t-tests, was used to compare satisfaction levels and identify key drivers of pilgrim experiences. Findings: The Jyotirlinga circuit demonstrated significantly higher satisfaction scores (M = 8.4/10) compared to RVGP (M = 7.1/10), attributed to superior infrastructure (roads, accommodation), effective signage, and robust promotional strategies. Conversely, RVGP—despite its cultural and spiritual significance—faced challenges in accessibility (30% dissatisfaction), transport (42% dissatisfaction), and visibility. Practical Implications: The findings underscore the need for targeted investments in RVGP’s infrastructure, digital promotion, and crowd management systems. For JYTP, sustaining visitor satisfaction requires addressing overcrowding (41% reported issue). Both circuits benefit from integrating community-driven tourism models to enhance inclusivity. Originality/Value: This study provides the first empirical comparison of RVGP and JYTP, offering actionable insights for balancing heritage preservation with modern tourism demands. It contributes to policy frameworks for sustainable religious tourism, particularly in underdeveloped pilgrimage corridors like RVGP.